Effectiveness of tisagenlecleucel versus real-world standard of care in relapsed/refractory follicular lymphoma - Yanni Hao; Wei-Chun Hsu; Craig S Parzynski; Evgeny Degtyarev; Lisa V Hampson; Aisha Masood; Wen-Hsing Wu (Becaris Publishing Limited, 2023)
Aim: To contextualize the effectiveness of tisagenlecleucel versus real-world standard of care (SoC) in relapsed/refractory follicular lymphoma. Materials & methods: A retrospective indirect matched comparison study using data from the phase II ELARA trial and the US Flatiron Health Research Database. Results: Complete response rate was 69.1 versus 17.7% and the overall response rate was 85.6 versus 58.1% in tisagenlecleucel versus SoC, post weighting by odds. For overall survival, an estimated reduction in the risk of death was observed in favor of tisagenlecleucel over SoC. The hazard ratio for progressionfree survival was 0.45 (95% CI: 0.26, 0.88), and for time-to-next treatment was 0.34 (95% CI: 0.15, 0.78) with tisagenlecleucel versus SoC. Conclusion: A consistent trend toward improved efficacy end points was observed in favor of tisagenlecleucel versus SoC.